"مدى التزام الشركات المدرجة في سوق دمشق للأوراق المالية بالإفصاح القطاعي وفقاً لمتطلبات المعيار الدولي لإعداد التقارير المالية IFRS(8) "القطاعات التشغيلية" " "دراسة تطبيقية" - يوسف, علي; صفا, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى بيان مدى التزام الشركات المدرجة في سوق دمشق للأوراق المالية بالإفصاح القطاعي وفقاً لمتطلبات المعيار الدولي لإعداد التقارير المالية IFRS(8)"القطاعات التشغيلية", إذ أن الإفصاح القطاعي يقدم تفصيلات أكثر للمعلومات المجمعة على المستوى الكلي للمنشأة, فقطاعات المنشأة في بعض الحالات تشبه وحدات مستقلة وكاملة لكل منها خصائصها الواجب الإفصاح عنها بشكل مستقل.من أجل ذلك قسَم البحث إلى جزأين: نظري وتطبيقي, تناول الباحث في الجزء الأول مفهوم الإفصاح القطاعي وطبيعة المعلومات التي يوفرها حول المنشأة , والتطور التاريخي للإفصاح القطاعي على صعيد معايير المحاسبة الدولية, ومن ثم عرض لمتطلبات المعيار IFRS(8)"القطاعات التشغيلية".أما الدراسة التطبيقية للبحث فجرت من خلال تحليل ومقارنة المعلومات القطاعية المفصح عنها في التقارير المالية للشركات المدرجة في سوق دمشق للأوراق المالية, مع المعلومات القطاعية المطلوب الإفصاح عنها وفقاً لمتطلبات المعيار IFRS(8) "القطاعات التشغيلية", وقد توصل الباحث إلى أن هناك شركتان من الشركات المدرجة لا تفصح عن أية معلومات قطاعية, كما أن الشركات المفصحة قطاعياً لا تمتثل بشكل تام لمتطلبات المعيار IFRS(8)وأن المعلومات القطاعية المفصح عنها هي أقرب لمتطلبات الإفصاح القطاعي وفق المعيار السابق IAS(14), حيث بينت نتائج الدراسة التطبيقية أن الشركات المدرجة في سوق دمشق للأوراق المالية تفصح عن أسس تحديد قطاعاتها التشغيلية المشمولة في التقارير المالية, كما أنها تفصح عن معلومات حول الربح أو الخسارة والإيرادات والمصاريف والأصول والالتزامات لقطاعاتها التشغيلية وفقاً لمتطلبات المعيار IFRS(8), في حين أنها لا تلتزم بالإفصاحات القطاعية المطلوبة على النطاق الكلي للمنشأة.This research aims to show the extent of the commitment of listed companies on the Damascus Securities Exchange of segment disclosure in accordance with the requirements of the International Financial Reporting Standard IFRS (8) "Operating Segments", as the segment disclosure provides more details of the information collected at the macro level of the facility, since the segments of facility in some cases, similar to an independent and complete units ,each with its own characteristics to be disclosed separately.This research is divided into two parts: Theoretical and Empirical, in the first part the researcher takes the concept of segment disclosure and the nature of the information provided about the facility, and the historical development of the segment disclosure at the level of international accounting standards, and then displays the requirements of the standard IFRS (8) "Operating Segments". The Empirical study is conducted by analyzing and comparing the disclosed segment information in the financial reports of the listed companies in the Damascus Securities Exchange, with the segment information required to be disclosed in accordance with the requirements of the standard IFRS (8) "Operating Segments", The researcher found that there are two companies from listed companies do not disclose any segment information, and that companies disclose about their segments, do not comply fully with the requirements of the standard IFRS (8) and segments information disclosed is the closest to the requirements of the segments disclosure in accordance with the previous standard IAS (14).The results of the empirical study showed that the listed companies in Damascus Securities Exchange disclose basis for the determination of operating segments covered in the financial reports, as it discloses information about profit or loss, income and expenses, assets and liabilities for its operating segments in accordance with the requirements of the standard IFRS (8), while they do not commit to segment disclosures required at the macro scale property.